2020
DOI: 10.4067/s0718-381x2020000200236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Retention of Conventional Dentures after the use of Common Adhesive Brands on Poor Denture Foundations. An in vitro Study

Abstract: There is no information about the possible impact in denture retention after the use of common denture adhesives (DAs) when poor denture foundations (PDF) are present. Moreover, there is a lack of information about which current formulation provides greater retention and for how long. Twelve models from edentulous patients with different ridge shape and border height were used and complete dentures were manufactured. Four different formulation brands of DAs were tested after 10 minutes and three, six, nine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…According to Johnson et al, the saliva used in a DA retention study is of crucial importance as in vivo retention depends on it. The use of artificial saliva is important due to its viscosity, as compared to studies using water [36,37]. The hydration time of the models and DA was 10 min, using the method described by Flores-León et al Saliva was maintained at 37 • C, reproducing the conditions of the oral cavity, as reported by Ikemura et al [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Johnson et al, the saliva used in a DA retention study is of crucial importance as in vivo retention depends on it. The use of artificial saliva is important due to its viscosity, as compared to studies using water [36,37]. The hydration time of the models and DA was 10 min, using the method described by Flores-León et al Saliva was maintained at 37 • C, reproducing the conditions of the oral cavity, as reported by Ikemura et al [30].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum force was recorded, and the retention force was calculated, according to tests performed by several authors [27,30]. The measurements were performed after the DA application and the following 10 min of hydration [37]. This selected time interval was based on several articles described in the literature and, according to ISO 10873, for type 1, class 2 dental adhesives [31,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ca/Zn partial salt of PVM‐MA provides a stronger longer‐term hold due to its lower water solubility level. This unique formulation warrants evaluation with respect to retention efficacy, because studies have shown that various adhesive formulations exhibit differential efficacy 15–18 …”
mentioning
confidence: 99%
“…This unique formulation warrants evaluation with respect to retention efficacy, because studies have shown that various adhesive formulations exhibit differential efficacy. [15][16][17][18] Gnathodynamometry is an established method of measuring maxillary denture retention. 11,12,19,20 In this method, study participants bite on the gnathodynamometer mouthpiece, which alters the length of the wire contained therein; the resultant differential resistance of the wire reflects the bite force.…”
mentioning
confidence: 99%